Optimasi Penggunaan Asap Cair pada Pengawetan Bakso Filler Roti - Sarono, Sarono (Jurnal Penelitian Pertanian Terapan, 2010)
Sweet bread is a very popular food in Indonesia and the quality is largely determined by the filler used. Today, the bread is very varied filler that are the fruit aroma to chopped meatballs. The meatballs as a filler of sweet bread can only self life for no longer than 2 days, therefore it needs a preservation effort. One of technical preservation was application of liquid smoke. The research objective was to characterize of the meatballs as filler and of liquid smoke of coconut cell and to know the effect of concentration of liquid smoke to self life of sweet bread filled meatballs in storage. The results showed that dipping the meatballs in a liquid smoke was lowered taste, but only slightly affected the color, surface mucus, texture, and preference until the third day. The higher concentration of liquid smoke was the lower of total microbes in the meatball during storage. Liquid smoke was not advisable as a preservative in bread balls for sweet bread filler, because the concentration of smoke liquid 2% only decreased the bread taste. Keywords: Liquid smoke and meatballs bread filler